Trechispora daweishanensis and T. xantha spp. nov. (Hydnodontaceae, Trechisporales) found in Yunnan Province of China - Zong, Tong-Kai; Liu, Chao-Mao; Wu, Jian-Rong; Zhao, Chang-Lin (Phytotaxa, 2021)
Two wood-inhabiting fungal species, Trechispora daweishanensis and T. xantha spp. nov. are proposed based on morphological features and molecular evidence. Trechispora daweishanensis is characterized by basidiomata with an annual growth habit, a tuberculate hymenophore, a monomitic hyphal system with clamped generative hyphae and ellipsoid, hyaline, thin-walled, smooth basidiospores measuring 3.8–5 × 2.7–3.5 µm. Trechispora xantha is characterized by resupinate, cracked basidiomata with a buff-coloured hymenial surface, a monomitic hyphal system and ellipsoid, hyaline, thin-walled, smooth basidiospores measuring 4.3–5.7 × 3.2–4 µm. Sequences of ITS and nLSU gene regions of the studied samples were generated. The phylogenetic analysis based on molecular data of ITS+nLSU sequences supported the novelty of these two species. Furthermore, we provide a key to the known species of Trechispora in China.